Metrology of additively manufactured lattice structures by X-ray tomography (Transactions on Additive Manufacturing Meets Medicine, 2020)
Additive manufacturing allows complexity of manufactured metal structures. Lattice structures hold the most promise for high complexity, tailorable and ultra-lightweight structures. In medical applications, these structures find application especially in bone implants – allowing matching of local elastic modulus of implant to that of bone while also allowing osseointegration. With this new complexity comes new manufacturing quality control and metrology challenges. Traditional metrology tools cannot access the entire structure and the only reliable method to inspect the inner details of these structures non-destructively is by X-ray tomography.
Keywords: metrology